Assessing the disability inclusiveness of university buildings in Hong Kong. Issue 2 (2nd April 2016) - Lau, Wai Kin; Ho, Daniel Chi Wing; Yau, Yung
ABSTRACT: Tended to view disability inclusion as merely another mandate, building and construction practitioners have yet to recognize its value in social sustainability. In academia, similarly, it has received less attention than other building performance attributes such as environmental friendliness and indoor air quality. With rights to access now acknowledged as basic human rights, there is demand for a tool to assess building disability inclusiveness, indicating the extent to which building considerations include persons with disabilities (PWDs). This paper proposes a Building Inclusiveness Assessment Score (BIAS) to fill the existing gap. The BIAS framework comprises two hierarchies of inclusion attributes identified from literature, guides, and standards of barrier-free access and universal design. The final product consists of two building disability inclusiveness assessment tools: the Physical Disability Inclusion Sub-score (PDIS) and the Visual Impairment Inclusion Sub-score (VIIS). These are simple, quantitative, objective tools for assessing buildings. We performed a Monte Carlo simulation to validate the assessment protocols. Following the validation, we assessed 48 university buildings at four universities in Hong Kong to illustrate the real-life application of the tools.